The identification of XPR1 as a voltage- and phosphate-activated phosphate-permeable ion channel - Hongjiang Wu; Liang Sun; Tong Huo; Theodore G. Wensel; Frank T. Horrigan; Zhao Wang (Nature Communications)
Abstract Maintaining a balance of inorganic phosphate (Pi) is vital for cellular functionality. Proper phosphate levels are managed through Pi import and export; and the processes governing Pi export remain the least understood. Xenotropic and Polytropic retrovirus Receptor 1 (XPR1) has been identified as the only known Pi export protein in mammals. In this study, we introduce the cryogenic electron microscopy structure of human XPR1 (hXPR1), unveiling a structural arrangement distinct from that of any known ion transporter. Our structural results suggest that hXPR1 may operate as an ion channel, a hypothesis supported by patch clamp recordings revealing hXPR1’s voltage- and Pi-dependent activity and large unitary conductance. Further analyses, including the structure of hXPR1 in presence of Pi, and mutagenesis studies at one of the putative Pi binding sites, lead us to propose a plausible ion permeation pathway. Together, our results provide novel perspectives on the Pi transport mechanism of XPR1.